Modeling and analysis of temporal dynamics in groundwater aquifers of New Valley Oases, Egypt - Abu-Bakr, Heba Abdel Aziz; Hegab, Mostafa G.; Al Zayed, Islam Sabry; Abd Elhamid, Ahmed Medhat Ismail (Brawijaya University, 2024)
Water scarcity poses a significant challenge in arid and semi-arid regions, necessitating a focused exploration of groundwater resources. Egypt, confronted with various water challenges, particularly in its Western Desert, relies heavily on groundwater as the exclusive water source due to the presence of the Nubian Sandstone aquifer. Effective groundwater management in this region is imperative. This study delves into the hydrogeological characteristics of the Nubian Sandstone aquifer system (NSAS) in the prominent New Valley Oases—Kharga, Dakhla, and Farafra—where agricultural activities heavily depend on groundwater. The primary objective entails a meticulous temporal assessment of the impact of groundwater development on aquifer behavior, groundwater levels, and drawdown. Employing a remote sensing approach, agricultural expansion from 1995 to 2020 was scrutinized. The Visual MODFLOW package served as a robust tool for simulating groundwater flow in the study areas. Noteworthy findings reveal an upward trajectory in agricultural crop areas, escalating by approximately 6% from 1740 km² in 1995 to 1850 km² in 2020. Concurrently, drawdown, influenced by current groundwater extraction, is anticipated to range from 0.5 to 5 meters per year. To ensure the sustainable development of these areas, stringent regulations must be implemented, underscoring the imperative for judicious groundwater management practices. This research underscores the critical need for informed decision-making and proactive measures to address the evolving dynamics of groundwater resources in the New Valley Oases.